Woman focused smoking cessation programming: a qualitative study. Issue 1 (December 2016) - Minian, Nadia; Penner, Jessica; Voci, Sabrina; Selby, Peter
Abstract Background Several studies of smoking cessation programs in clinical settings have revealed poorer outcomes for women compared to men, including counselling alone or in combination with pharmacotherapy. The objective of the current study was to explore treatment and program structure needs and preferences among female clients in a specialized smoking cessation clinic in an academic mental health and addiction health science centre in order to inform program design so that it meets the needs of female clients. Methods Four focus groups were conducted with current and former female clients (n  = 23, mode age range = 50–59 years old, 56.5 % were still smoking and 43.5 % had quit) who had registered for outpatient smoking cessation treatment. Questions were designed to examine what aspects of the services were helpful and what changes they would like to see to better assist them and other women with quitting smoking. A thematic analysis of the raw data (audio recordings and notes taken during the focus groups) was conducted using a phenomenological theoretical framework. Results Themes that emerged indicated that females trying to quit smoking are best supported if they havechoice from a variety of services so that treatment can be individualized to meet their specific needs; psychosocialsupport is provided both one-one-one with health care professionals and by peers in support groups;free pharmacotherapy is available to eliminate financial barriers to use;women-specific educational topics and support groups are offered; the clinic isaccessible with evening/weekend hours, options to attend a local clinic, and childcare availability; andcommunication about clinic services and operation are clear, readily available, and regularly updated. Conclusions An ideal smoking cessation program for women includes a women's centred approach with sufficient variety and choice, free pharmacotherapy, non-judgmental support, accessible services and clear communication of program options and changes. Findings may suggest an actionable list of adaptations that can be adopted by other clinics providing smoking cessation services to women.